Comparative Analysis of Venture Studios and Venture Capital - Shamsiddinov, Muhiddinxuja (2025)
This thesis presents a comparative analysis of two prominent early-stage venture creation models (venture studios and traditional venture capital) and examines how each influences innovation, entrepreneurial processes, and startup success. Employing a mixed-methods approach, the research integrates quantitative analysis of performance metrics (including time-to-funding milestones, success and failure rates, and investor returns) with qualitative insights from semi-structured interviews with practitioners from leading venture building firms. Findings reveal that venture studios accelerate time-to-market and achieve higher early-stage survival and exit rates through intensive operational support and rigorous internal vetting. Conversely, traditional venture capital offers broader portfolio diversification, greater founder autonomy, and deeper access to follow-on growth capital, which can be critical for radical or long-horizon innovations. Qualitative evidence suggests that studios excel at systematic, execution-driven innovation by providing turnkey resources and repeatable playbooks, while VCs foster entrepreneurial creativity and independence. The thesis concludes that both models play complementary roles within startup ecosystems: venture studios are optimal for rapid validation and resource-constrained founders, whereas venture capital is best suited for scaling founder-led breakthroughs. Recommendations are offered to guide founders, investors, and policymakers in selecting and supporting the model that aligns with their strategic objectives.